Eating disorders, body dysmorphic disorder, and body image pathology in female Australian models. (5th February 2020) - Collison, James; Barnier, Ellise
Abstract: Objective: Female models are commonly viewed as "at‐risk" for eating and body image disorders. However, the existing literature is sparse and provides inconsistent evidence. It subsequently fails to decipher whether models are truly at any greater risk for body image disorders than non‐models. Such discrepancies may exist due to differences in population, method, and assessment, particularly where previous studies have focused on evaluative body image that mostly reflect normative body image concerns. This study sought to examine body image disturbance, dysmorphic appearance concern, the rate of probable eating disorders (EDs) and body dysmorphic disorder (BDD), depression, anxiety, stress, self‐esteem, and functional impairment in models. Method: A sample of 100 female models was compared to 100 age‐matched tertiary students on measures of ED symptoms, body dysmorphic symptoms, psychopathology, and functional impairment. Results: Ninety‐two models met referral criteria for an ED and 26 for non‐weight related BDD, compared to 53 (ED) and 2 (BDD) students. Models also reported greater body image disturbance, dysmorphic appearance concern, depression, stress, functional impairment, and ED symptoms, but equivalent degrees of anxiety, self‐esteem, and home‐based functional impairment. Conclusions: Not only are female models at‐risk of the physical effects of maintaining a clinically underweight body, but models are at greater risk of developing body image‐related psychological illnesses, experiencing emotional stressors, and facing functional impairment than their non‐model peers.